Developing Children’s Financial Quotient (FQ) Through the ‘Tangga Uang’ Educational Game - Suryanto, D; Gideon, H; Dewi, M K (KnE Social Sciences, 2018)
Financial literacy needs to be given since childhood because it will make individual growth easier to understand financial intelligence and life skills. The form of the game has an important role in internalizing the values to be invested. The game of money ladder has the advantage of side; design logo, color, content and message of education, psychology. The results shown from the games played by children that children begin to enjoy simple knowledge related to financial literacy. The role of the family remains necessary to accompany and explain knowledge into simple language. Keywords: Financial literacy, Motor psychology of children, The game of money ladder